Uterine and Ovary Carcinosarcomas. (June 2015) - Pacaut, Cécile; Bourmaud, Aurélie; Rivoirard, Romain; Moriceau, Guillaume; Guy, Jean-Baptiste; Collard, Olivier; Bosacki, Claire; Jacquin, Jean-Philippe; Levy, Antonin; Chauleur, Céline; Magné, Nicolas; Merrouche, Yacine
<x xml:space="preserve">Abstract</x> Objectives: The aim of this study was to assess the outcome and the prognosis factors of uterine and ovarian carcinosarcomas. Methods: From January 1993 to January 2010, data from 68 consecutively treated patients with uterine (n=59) and ovarian (n=9) carcinosarcomas were retrospectively analyzed in a single French comprehensive cancer center. Results: The median follow-up was 24.2 months (interquartile range [IQR]: 13.5 to 54.6). The median age was 69 years (IQR: 63 to 77). Patients were classified as FIGO stage I (n=28; 41%) and FIGO stage II to IV (n=40; 59%), respectively. There were 33 (49%) and 29 (43%) homologous and heterologous type, respectively. The median disease-free survival and overall survival were 21.9 months (IQR: 7.9 to 22.3) and 27.1 months (IQR: 14.5 to 72), respectively. No statistical differences of survival were reported concerning the initial location of the carcinosarcoma (uterine vs. ovarian). Radiation therapy (hazards ratio [HR]=0.3; 95% confidence interval [CI], 0.16-0.67) and FIGO stage I (HR=0.4; 95% CI, 0.17-0.9) were associated with an increased disease-free survival. Homologous type (HR=3; 95% CI, 1.4-6.3) and FIGO stage II to IV (HR=2.64; 95% CI, 1.3-5.4) were associated with a decreased overall survival. There was no survival improvement for the 12% of patients receiving a multimodal adjuvant therapy. Conclusions: Uterine and ovary carcinosarcomas present a worse prognosis. On the basis of the present study data, although it should be prospectively confirmed, a sequential or multimodal adjuvant therapy should be proposed to patients with early-stage uterine and ovary carcinosarcomas.